Daralo Song Composition: Mebawalase Mesampere Style - Lawendatu, Frangky; Batubara, Junita; Lestari, Dewi Tika (Jurnal Riset Ilmu Pendidikan, 2025)
This study highlights the culture of the Sangihe Talaud community, regarding the M?samper? song. M?samper? is the ancestral culture of the Sangihe community which has been passed down from generation to generation until now. The Sangihe Islands are one of the islands located in North Sulawesi Province. The term Mebawalase Mesampere means to reply in the Sangihe language, which is a singing style where the singers will reply to each other's songs (like replying to pantun). Daralo is a song composition inspired by Mebawalase Mesampere. Researchers found several styles of Mebawalase Mesampere singing in the work of daralo. Researchers also found that the creators of Mebawalase Mesampere songs did not include their names or were anonymous, so that the Mebawalase Mesampere-style songs that were created will gradually become extinct. This study uses qualitative methods with data analysis and interviews. In terms of the creation of Daralo, the style of the song Mebawalase Mesampere is performed using western musical instruments, so that the nuances of the song that characterize Mebawalase Mesampere are more creative and innovative. The results of the study have been performed at STT Jaffray Makassar in a recital as a requirement for the final exam for the concentration of church music.